PENGARUH KEMAMPUAN KERJA PEGAWAI DAN KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT PADA SEKRETARIAT KECAMATAN SUSOH KABUPATEN ACEH BARAT DAYA - Qibtiah, Faras Mariatul; Ertika, Yenny (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Public service by the State Civil Apparatus (ASN) has now become a strategic issue, because the level of performance quality in public services will determine whether or not service to the community is good. This research was approached with quantitative descriptive data. This study aims to determine and explain the effect of employee work ability and quality of public services on community satisfaction at the Secretariat of Susoh District, Southwest Aceh Regency. The research variables are work ability (X1), service quality (X2) and community satisfaction (Y). The research method used is a quantitative method with associative type which explains the relationship between the independent variable and the dependent variable. The results of distributing questionnaires with the community who came to the Camat Office to take care of their interests, most of them gave positive answers both in terms of service.